2014
DOI: 10.1039/c4nr00402g
|View full text |Cite
|
Sign up to set email alerts
|

Nano-ceramic support materials for low temperature fuel cell catalysts

Abstract: Low temperature fuel cells (LTFCs) have received broad attention due to their low operating temperature, virtually zero emissions, high power density and efficiency. However, the limited stability of the catalysts is a critical limitation to the large scale commercialization of LTFCs. State of the art carbon supports undergo corrosion under harsh chemical and electrochemical oxidation conditions, which results in performance degradation of catalysts. Therefore, non-carbon materials which are highly oxidation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 136 publications
0
60
0
Order By: Relevance
“…A strong metal-support interaction (SMSI) between Pt and ceramic supports has been used to simultaneously improve the activity and durability of Pt catalysts [16,17]. A strong interaction usually increases the Pt dispersion and causes the lower particle aggregation, because small Pt nanoparticles are more strongly anchored to the support.…”
Section: Introductionmentioning
confidence: 99%
“…A strong metal-support interaction (SMSI) between Pt and ceramic supports has been used to simultaneously improve the activity and durability of Pt catalysts [16,17]. A strong interaction usually increases the Pt dispersion and causes the lower particle aggregation, because small Pt nanoparticles are more strongly anchored to the support.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include its use as a substrate for group III nitride semiconductors in optoelectronic devices [1][2][3][4][5] , as support material for low-temperature fuel cells 6,7 , and as a hydrogen storage medium 8 . Difficulties associated with synthesis, however, have hindered broad adoption of the material -production of high-density ZrB 2 typically requires both extremely high temperature and pressure 9 because of its high melting point and stability.…”
mentioning
confidence: 99%
“…It was shown that no change in the redox region occurred after 48 h oxidation treatment for nano-ZrO 2 ceramic [141]. Furthermore, different electrochemical inert ceramics including metal oxides (TiO 2 ), nitrides (TiN, ZrN), borides (TiB 2 ) and carbides (TaC) are reported as stable replacements for traditional carbon black support [103,135]. In a comparative study, TiO 2 supported Pt electrocatalyst showed promising stability when aged at 1.2 V for a corrosion time of 200 h, whereas the carbon supported Pt electrocatalyst degraded within 80 h [98].…”
Section: Stability Of Catalysts In Fuel Cellsmentioning
confidence: 96%
“…Pt based nanoparticles are reported to be degrading under electrochemical oxidation conditions and corrosive environment due to decrease in chemical surface area, particles aggregation or migration, dissolution or redeposition (Oswald ripening process) and detachment due to corrosion of the C support [135,136,75,137,138]. Ultrathin Pt monolayer shell Pd nanowire core catalysts have shown excellent electrochemical stability under accelerated half-cell testing with an increase in area-specific activity by 1.5-folds [139].…”
Section: Stability Of Catalysts In Fuel Cellsmentioning
confidence: 97%